Understanding the (Im)mobilities of Engaging At-Risk Youth Through Art and Mobile Media. (2nd July 2016) - Castro, Juan Carlos; Lalonde, Martin; Pariser, David
Abstract : Teens in high school who have or are at-risk of dropping out of school confront a number of educational challenges. One of these challenges is the restricted mobility students face in school. Mobile media offers the potential to engage with art curricula inside or outside of the classroom. It also offers new ways of thinking about the role of mobility in learning and improving students' sense of agency. In this study, we present our research with at-risk youth, who typically associated traditional schooling with a low sense of personal agency and spatial constraints. To judge by their responses (visual and verbal) to our mobile media visual art curriculum, the physical mobility afforded by mobile technology heightened their sense of agency and opened them to the possibility that learning might be a positive experience, and that they might want to be at school.